2022
DOI: 10.1021/acs.inorgchem.2c02897
|View full text |Cite
|
Sign up to set email alerts
|

Manipulating the Spin State of Fe Sites via Fe–O–Si Bridge Bonds for Enhanced Polysulfide Redox Kinetics in the Li–S Battery

Abstract: Transition metals with 3d unoccupied orbitals have superior catalytic activity, but inherent high spin suppresses their adsorption capability, leading to sluggish polysulfide conversion kinetics for Li−S batteries. Herein, we provide Fe−O−Si bridge bonds to manipulate e g filling and induce a high-to-medium spin transition of Fe 3+ sites, which enhances polysulfide adsorption and facilitates sulfur redox reaction kinetics. The resultant cathodes exhibit outstanding performances under high sulfur loading, which… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 49 publications
0
5
0
Order By: Relevance
“…The inclusion of quantum correlations in catalytic design is essential if we consider that novel predictors mainly based on spin-potentials from open-shell orbitals have already contributed to identify magnetic material combinations that exhibit OER activities at least one order of magnitude larger than that of IrO 2 (usually identified as the state-of-the-art in industrial OER). 11,97–99 These advances will reduce the gap between fundamental research and applied technology for clean energy, 15,43,100–103 and we are moving towards a ±0.1 V error in the computational accuracy of reaction pathways when comparing and screening active catalysts. Likewise, accurate computational chemistry can also deliver improvements in noble metal based catalysts utilised in PEM_EL, by maximising the efficiency and concomitantly lowering the Pt content, via orbital engineering of magnetic elements, as in the case of Pt 3 Co. 52,53…”
Section: Discussion and Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The inclusion of quantum correlations in catalytic design is essential if we consider that novel predictors mainly based on spin-potentials from open-shell orbitals have already contributed to identify magnetic material combinations that exhibit OER activities at least one order of magnitude larger than that of IrO 2 (usually identified as the state-of-the-art in industrial OER). 11,97–99 These advances will reduce the gap between fundamental research and applied technology for clean energy, 15,43,100–103 and we are moving towards a ±0.1 V error in the computational accuracy of reaction pathways when comparing and screening active catalysts. Likewise, accurate computational chemistry can also deliver improvements in noble metal based catalysts utilised in PEM_EL, by maximising the efficiency and concomitantly lowering the Pt content, via orbital engineering of magnetic elements, as in the case of Pt 3 Co. 52,53…”
Section: Discussion and Resultsmentioning
confidence: 99%
“…The inclusion of quantum correlations in catalytic design is essential if we consider that novel predictors mainly based on spin-potentials from open-shell orbitals have already contributed to identify magnetic material combinations that exhibit OER activities at least one order of magnitude larger than that of IrO 2 (usually identified as the state-of-the-art in industrial OER). 11,97-99 These advances will reduce the gap between fundamental research and applied technology for clean energy, 15,43,[100][101][102][103] and we are moving towards a ±0.1 V error in the computational accuracy of reaction pathways when comparing and screening active catalysts. Likewise, accurate computational chemistry can also deliver improvements in noble metal based catalysts utilised in PEM_EL, by maximising the efficiency and concomitantly lowering the Pt content, via orbital engineering of magnetic elements, as in the case of Pt 3 Co. 52,53 Because there is no clear indication at the present time of which WEL technology will become dominant in the near future (although PEM_EL might be the technology of choice when coupled to highly volatile renewables) 63 specific developments and optimisation methods should not be limited to a single technology, but they should be extended to all six possible (different) catalytic interphases (i.e., three set ups previously seen for HER and OER).…”
Section: Catalysis Science and Technologymentioning
confidence: 99%
“…More recently, versatile spin electrocatalysis has been in full swing and helped integrate a comprehensive understanding of sulfur redox. [ 109–112 ]…”
Section: Comparison Of Various Field‐assisted Electrocatalysismentioning
confidence: 99%
“…More recently, versatile spin electrocatalysis has been in full swing and helped integrate a comprehensive understanding of sulfur redox. [109][110][111][112] Meanwhile, our group took full advantage of spinel-type electrocatalysts with tetrahedral (Td) and octahedral (Oh) configuration simultaneously, plowing a universal concept of geometrical-site-dependent electrocatalytic activity to enrich the scope of applications for spin manipulation (Figure 4D). [103] Once Mn 3+ is incorporated into Oh sites in antiferromagnetic Co Oh -O-Co Td backbones, the originally located Co 3+ Oh is driven into Td sites to construct ferromagnetic Mn 3+ Oh -O-Co 3+ Td backbones instead.…”
Section: Spin Polarization Reinforcing Lipss Interactionmentioning
confidence: 99%
“…It is widely accepted that the spin state configuration of 3d transition metals can be a critical catalytic descriptor in electrocatalytic and photocatalytic systems. This is because spin state configuration is an index of the overall structure, energy, and redox profile of the catalyst, which determines the occupancy of e g orbital and impacts key reaction steps. ,, The spin state of transition-metal atom can be rationally modulated by the ligand field, magnetic field, or stress field. , Zhang et al have found that the Co atom experiences a transition from low-spin to high-spin states, generating more unpaired electrons under an external magnetic field . Such spin delocalization increases the charge transfer and orbital interactions between the sulfur species and the catalyst, thus lowering the energy barrier and increasing the reaction kinetics.…”
Section: Introductionmentioning
confidence: 99%